PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA TOKO SECONDARYSHOE DI MEDAN - Lisa Lutfiyah Nasution; Ramadhan Ramadhan; Hernawaty Lubis (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
This study plans to decide whether the nature of the goods and the administration at the same time affect the fulfillment of buyers at a Secondary Shoe Store in Medan. The information inspection procedure used is a quantitative introduction technique with the help of the SPSS program. This study used different straight recurrences. Exploratory test as many as 83 respondents. Lots of important information using polls. The results showed that the quality of goods to a certain degree affect the fulfillment of shoppers at the Secondary Shoe Store in Medan. Administration to some extent affects consumer loyalty at the Secondary Shoe Store in Medan. The nature of goods and administration at the same time affect the fulfillment of shoppers at the Secondary Shoe Store in MedanKeywords: Product Quality, Service and Satisfaction.